Ernesto Nathan Rogers - Deregibus, Carlo (Philosophy Kitchen - Rivista di filosofia contemporanea, 2024)
The privilege of any artistic practice is to continuously, and mostly unconsciously, draw on the inexhaustible repertoire of the past, recreating it from the point of view of present contingency and future extension. It is a political use of facts, concepts, figures, writings and, above all, forms, which feeds on a potentially infinite analogical logic in order to re-found itself again and again, seeking a necessity in new configurations of the real. Of course, that architecture is an artistic practice is widely disputed and, in any case, its spurious character, caught between classical Vitruvian values and an increasingly recalled socio-technical dimension, certainly makes it unsuitable for reasoning by absolute ideals.